Interplaying factors of group size and personality attributes of EFL students in using process approach to writing - Hashim, Siti Noor Aneeis; Mohamad, Mafuzah; Hajimia, Hafizah; Abdul Kadir, Abdul Halim; Nasir, Farhana; Yusof, Syahidah Sofia (NeuroQuantology, 2022)
This research looked at group size and personality characteristics on learners' collaborative writing skills. A quasi-experimental technique utilized a non-randomized pre-test and post-test group. Three classes of 113 students took part in this research. The primary group of students (40 students) was given to produce explanation essays in pairs utilizing the process writing method. The writing work was done by the second class (33 students), with four students per group using the same writing style. The third session (40 students) used the process writing technique to write essays independently. Each of the three courses includes 10 hours of instruction, including a pre-and post-test. Students in pairs and teams had to fill out a personality type questionnaire to determine whether they were extroverted or introverted. The students' post-test results were compared using a one-way ANOVA and an independent sample t-test. The research findings revealed that students who worked in pairs or groups were better writers than alone. It was also discovered that students who worked in tandem outperformed students who worked in teams. Finally, there was no discernible difference in writing abilities among extrovert and introvert students when they cooperated in pairs or groups.